Invisible Reconstruction Cross-disciplinary responses to natural, biological and man-made disasters - Patrizio Gunning, Lucia; Rizzi, Paola (FRINGE, 2022)
What does it really mean to reconstruct a city after a natural, biological or man-made disaster? Is the repair and reinstatement of buildings and infrastructure sufficient without the mending of social fabric? The authors of this volume believe that the true measure of success should be societal. After all, a city without people is no city at all. Invisible Reconstruction takes the view that effective disaster mitigation and recovery require interdisciplinary tactics. Historian Lucia Patrizio Gunning and urbanist Paola Rizzi expand beyond the confines of individual disciplines or disaster studies to bring together academics and practitioners from a wide variety of disciplines, comparing strategies and outcomes in different scenarios and cultures from South America, Europe and Asia. From cultural heritage and public space to education and participation, contributors reflect on the interconnection of people, culture and environment and on constructive approaches to strengthening the intangible ties to increase resilience and reduce vulnerability. By bringing practical examples of how communities and individuals have reacted to or prepared for disaster, the publication proposes a shift in public policy to ensure that essential physical reinforcement and rebuilding are matched by attention to societal needs. Invisible Reconstruction is essential reading for policymakers, academics and practitioners working to reduce the impact of natural, biological and man-made disaster or to improve post-disaster recovery.